2019
DOI: 10.3233/ch-180469
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell deformability is diminished in patients with Chronic Fatigue Syndrome

Abstract: BACKGROUND: Myalgic encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a poorly understood disease. Amongst others symptoms, the disease is associated with profound fatigue, cognitive dysfunction, sleep abnormalities, and other symptoms that are made worse by physical or mental exertion. While the etiology of the disease is still debated, evidence suggests oxidative damage to immune and hematological systems as one of the pathophysiological mechanisms of the disease. Since red blood cells (RBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 16 publications
0
42
0
Order By: Relevance
“…RBC deformability has been shown to be affected by ALT [34], AST [35], CRP [36], and 25-OH vitamin D levels [37]. Interestingly, recently, RBC deformability has been found to be impaired also in patients with chronic fatigue syndrome [38].…”
Section: Discussionmentioning
confidence: 99%
“…RBC deformability has been shown to be affected by ALT [34], AST [35], CRP [36], and 25-OH vitamin D levels [37]. Interestingly, recently, RBC deformability has been found to be impaired also in patients with chronic fatigue syndrome [38].…”
Section: Discussionmentioning
confidence: 99%
“…6A-C). Ramasubramanian et al has reported higher levels of reactive oxygen species (ROS) in red blood cells of ME-patients compared to healthy controls (43), and up-regulation of the Oxidative stress response pathway upon INMEST (SIRT1), corroborates this observation. These upregulated pathways and the induction of genes in the insulin receptor signaling pathway, Heat shock proteins, and cell cycle regulators all support the idea that INMEST treatment upregulates disease tolerance pathways normally induced during infections, and possibly improperly suppressed in ME-patients ( Fig.…”
Section: Me -A Failure Of Inducing Disease Tolerance Upon Chronic Immmentioning
confidence: 82%
“…Polymers such as Polytetrafluoroethylene (PTFE), Poly (methyl methacrylate) (PMMA), Polydimethylsiloxane (PDMS) are also being used as substrates to fabricate these devices. Polymers are inexpensive and microchannels are created by embossing and molding (Saha et al, 2017b , 2019 ). Due to low autofluorescence, biocompatibility, non-toxicity, curing at low temperatures, PDMS is the most commonly used polymer.…”
Section: Commonly Used Fabrication Techniques For Poct Devicesmentioning
confidence: 99%